CLIMATIC FACTORS AFFECTING THE DEVELOPMENT OF EARLY SOYBEAN ACCESSIONS IN THE ENVIRONMENTS OF THE RUSSIAN NORTHWEST - I. V. Seferova; L. Y. Novikova (Труды по прикладной ботанике, генетике и селекции)
Climate requirements of early soybean forms have been evaluated in the planting-shooting and shooting-flowering interphase periods under the conditions of the Russian Northwest. The mean temperature is the principal factor regulating the duration of these periods. The duration of the period from planting to shooting within the interval from 10°C to 19°C has reduced with the growth of mean temperatures, and at temperatures above 19°C becomes constant (minimum). The duration of the period from shooting to flowering has reduced with the growth of temperatures, and for several accessions has become constant at temperatures above 19°C. Another, though less important factor determining the duration of these periods is rainfall. Absence of rainfall at the planting phase delays germination. Excessive rainfall in the shooting-flowering period delays the beginning of flowering.